Remittance markets in Africa - Mohapatra, Sanket, 1975-; Ratha, Dilip (Directions in development (Washington, D.C.). Finance., 2011)
Remittances sent by African migrants have become an important source of external finance for countries in the Sub-Saharan African region. In many African countries, these flows are larger than foreign direct investment and portfolio debt and equity flows. In some cases, they are similar in size to official aid from multilateral and bilateral donors. Remittance markets in Africa, however, remain less developed than other regions. The share of informal or unrecorded remittances is among the highest for Sub-Saharan African countries. Remittance costs tend to be significantly higher in Africa both for sending remittances from outside the region and for within-Africa (South-South) remittance corridors. At the same time, the remittance landscape in Africa is rapidly changing with the introduction of new remittance technologies, in particular mobile money transfers and branchless banking. This book presents findings of surveys of remittance service providers conducted in eight Sub-Saharan African countries and in three key destination countries. It looks at issues relating to costs, competition, innovation and regulation, and discusses policy options for leveraging remittances for development in Africa.